The Relationship Between Sharia And Human Rights In The Constitutions of Muslim-Majority States: Comparative Study of Indonesia, Malaysia, and Egypt - Khoiru Khoiru Turmudzi; Prayudi Rahmatullah (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
This research examines the legal issue concerning the constitutional relationship between Sharia law and human rights in Muslim-majority states. The study aims to analyze how Indonesia, Malaysia, and Egypt integrate Sharia principles into their constitutional frameworks while balancing them with the protection of individual human rights. This research employs normative legal research using a comparative approach. The findings reveal that each country adopts a distinct constitutional model that significantly influences the degree of human rights protection. Indonesia applies a moderate constitutional approach by positioning Sharia as a moral and cultural reference rather than as a formally supreme legal source, thereby allowing broader accommodation of international human rights norms. Malaysia institutionalizes Sharia within a dual legal system alongside civil law, which generates structural and normative tensions, particularly in legal disputes related to gender equality, freedom of religion, and personal status law. In contrast, Egypt constitutionally recognizes Sharia as a principal source of legislation, resulting in a stronger influence of religious norms on constitutional interpretation and a higher potential for normative conflict with international human rights standards. The study demonstrates that the constitutional positioning of Sharia plays a decisive role in shaping the scope and effectiveness of human rights protection. It further emphasizes the importance of continuous constitutional interpretation and legal reform to ensure coherence between Sharia-based norms and universally recognized human rights principles.